2021
DOI: 10.1016/j.jtho.2021.07.035
|View full text |Cite|
|
Sign up to set email alerts
|

Brigatinib Versus Crizotinib in ALK Inhibitor–Naive Advanced ALK-Positive NSCLC: Final Results of Phase 3 ALTA-1L Trial

Abstract: Introduction:In the phase 3 study entitled ALK in Lung cancer Trial of brigAtinib in 1st Line (ALTA-1L), which is a study of brigatinib in ALK inhibitor-naive advanced ALKpositive NSCLC, brigatinib exhibited superior progressionfree survival (PFS) versus crizotinib in the two planned interim analyses. Here, we report the final efficacy, safety, and exploratory results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
228
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 232 publications
(248 citation statements)
references
References 21 publications
18
228
1
1
Order By: Relevance
“… 9 Similarly, in the ALTA-1L trial, brigatinib demonstrated an OR of 74% compared to 62% with crizotinib and an HR for disease progression or death of 0.48. 17 Acknowledging the limitations of cross-trial comparisons, lorlatinib had a lower HR for disease progression or death of 0.28 relative to alectinib and brigatinib. 11 …”
Section: Systemic Response Of Lorlatinib In Advanced Alk-positive Nsclcmentioning
confidence: 99%
See 1 more Smart Citation
“… 9 Similarly, in the ALTA-1L trial, brigatinib demonstrated an OR of 74% compared to 62% with crizotinib and an HR for disease progression or death of 0.48. 17 Acknowledging the limitations of cross-trial comparisons, lorlatinib had a lower HR for disease progression or death of 0.28 relative to alectinib and brigatinib. 11 …”
Section: Systemic Response Of Lorlatinib In Advanced Alk-positive Nsclcmentioning
confidence: 99%
“… 17 Acknowledging the limitations of cross-trial comparisons, lorlatinib had a lower HR for disease progression or death of 0.28 relative to alectinib and brigatinib. 11 …”
Section: Systemic Response Of Lorlatinib In Advanced Alk-positive Nsclcmentioning
confidence: 99%
“…Although OS data were still maturing, posthoc analyses suggested, in patients with baseline brain metastases, an OS benefit for brigatinib (HR, 0.43). 32 …”
Section: Alta-1l Trialmentioning
confidence: 99%
“…The median PFS and ORR for patients treated with brigatinib was 24 months and 74%, respectively, compared with 11.1 months and 62% for those treated with crizotinib, respectively. 161 With longer follow‐up, patients with brain metastasis have benefited more from brigatinib treatment compared with crizotinib treatment. 161 In preclinical studies, brigatinib showed potential to overcome the ceritinib‐ or alectinib‐resistance mutations, including G1202R, F1174C/V, and I1171N/T/S.…”
Section: Targeted Therapy For Nsclcmentioning
confidence: 99%
“… 161 With longer follow‐up, patients with brain metastasis have benefited more from brigatinib treatment compared with crizotinib treatment. 161 In preclinical studies, brigatinib showed potential to overcome the ceritinib‐ or alectinib‐resistance mutations, including G1202R, F1174C/V, and I1171N/T/S. 162 …”
Section: Targeted Therapy For Nsclcmentioning
confidence: 99%